Cognitive Semantics Quest for the Ultimate Source Domain - Drogosz, Anna Maria (Acta Neophilologica, 2023)
The paper is an attempt to answer the question asked in Cognitive Semantics: Which experiential domain should be considered to be more fundamental or “ultimate”: space, an object or a human being? It is argued that they represent three domains of behaviour identified by archaeologists (the technical domain, the domain of social relations, and the natural history domain), and consequently are equally ultimate. It is also argued that the ability to project knowledge from one domain to the other was the crucial stage in the development of metaphor and abstract thinking, and that this ability (called cognitive fluidity or conceptual integration) was exapted from the physical to abstract domain.